A199 EFFICACY OF TOFACITINIB RETREATMENT FOR ULCERATIVE COLITIS AFTER TREATMENT INTERRUPTION: RESULTS FROM THE OCTAVE CLINICAL TRIALS. (1st March 2018) - Panés, J; Bressler, B; Colombel, J F; Lawendy, N; Maller, E; Zhang, H; Woodworth, D; Chan, G; Su, C
Abstract: Background: Tofacitinib is an oral, small molecule JAK inhibitor that is being investigated for ulcerative colitis (UC). It is not expected to elicit formation of neutralizing anti-drug antibodies that may limit successful retreatment after treatment interruption. Aims: To evaluate the efficacy of tofacitinib retreatment following treatment interruption in patients (pts) with UC participating in an ongoing Phase 3, open-label, long-term extension (LTE) study (OCTAVE Open, NCT01470612; data as of July 2016). Methods: The OCTAVE clinical trial program included induction (OCTAVE Induction 1 & 2), 1 maintenance (OCTAVE Sustain) 1 and LTE (OCTAVE Open) studies. OCTAVE Open included non-responders from OCTAVE Induction 1 & 2 and pts who completed or experienced treatment failure in OCTAVE Sustain. This analysis included the subpopulation of pts in OCTAVE Open who achieved clinical response (≥3-point and 30% reduction from induction baseline total Mayo score plus decrease ≥1 point in rectal bleeding subscore [RBS] or absolute RBS ≤1) following 8 weeks (wks) of induction therapy with tofacitinib 10 mg twice daily (BID), entered OCTAVE Sustain and experienced treatment failure while receiving placebo for up to 52 weeks and subsequently entered OCTAVE Open and received tofacitinib 10 mg BID. Treatment failure was defined by increase ≥3 points from maintenance study baseline total Mayo score plus increase in both RBS and endoscopic subscore (ES) ≥1 point; ≥8 wks of maintenance therapy. We evaluated rates of clinical response, mucosal healing (ES ≤1) and remission (total Mayo score ≤2, no individual subscore >1 and RBS=0) at Months (M) 2 and 12 of the LTE study using non-responder imputation (NRI). Results: Of 914 pts enrolled in OCTAVE Open and treated for ≥2 M at data cut-off, 101 entered OCTAVE Open with clinical response to tofacitinib 10 mg BID in OCTAVE Induction 1 or 2 and treatment failure with PBO during OCTAVE Sustain. Clinical response, mucosal healing and remission rates were, respectively, 75.8%, 55.4% and 40.4% at M2, and 67.5%, 53.6% and 43.4% at M12 (Table). Conclusions: For pts who responded to induction therapy with tofacitinib 10 mg BID and subsequently experienced treatment failure while receiving PBO maintenance therapy, efficacy responses were recaptured by a majority of pts by M2 and generally sustained at M12 after reinitiating tofacitinib 10 mg BID. Safety data were not presented for the retreatment subpopulation, limiting assessment of whether tofacitinib can be re-introduced safely in these pts. 1. Sandborn WJ et al. N Engl J Med 2017;376:1723–36. Funding Agencies: Pfizer Inc